Bullying Depicted in the Novel Big Girl by Danielle Steel - Tri Devi Purnama Sari Mizan (Paradigma Lingua, 2025)
This study aims to analyze how differences in the main character trigger acts of bullying as portrayed in Danielle Steel’s novel Big Girl, which centers on the character Victoria Dawson. The analysis applies Olweus’s (1993) theory of bullying to support the discussion of the bullying issues presented in the novel. This research employs a qualitative descriptive method to examine the character’s experiences and the underlying causes of bullying. The findings reveal that the main character, Victoria Dawson, becomes a victim of bullying due to her physical differences from her family members. She experiences emotional abuse and verbal humiliation from both her parents and people around her, particularly related to her body weight and appearance. These experiences lead to anxiety and low self-esteem, as her parents continually criticize her and pressure her to be thin. However, as the story progresses, Victoria develops courage and self-confidence, enabling her to resist bullying and affirm her self-worth.